Pengaruh Pembiayaan Qardhul Hasan terhadap Pertumbuhan Ekonomi Masyarakat Desa Padang Garugur Jae Kecamatan Aek Nabara Barumun Kabupaten Padang Lawas - Heriyanti Pasaribu; Enni Efrida Nasution; Aminah Lubis (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
This research aims to: (1) determine the effect of qardhul hasan financing on the economic growth of the people of Padang Garugur Jae village, Aek Nabara Barumun District, Padang Lawas Regency. (2) find out whether there is a significant influence between qardhul hasan financing on the economic growth of the people of Padang Garugur Jae village, Aek Nabara Barumun District, Padang Lawas Regency. Based on the research results, it can be concluded that: 1) The influence of qardhul hasan financing on empowering the economic growth of the Padang Garugur Jae village community, Aek Nabara Barumun District, Padang Lawas Regency can be seen from the results of the t-test on the qardhul hasan financing variable, tcount<ttable or 1.047<2.007 which shows Ho is rejected and Ha is accepted. The decision to reject Ho means that there is a significant positive relationship or influence between qardhul hasan financing and the economic growth of the Padang Garugur Jae village community. 2) The significant influence of qardhul hasan financing on the economic growth of the people of Padang Garugur Jae village, Aek Nabara Barumun District, Padang Lawas Regency can be seen from the results of the influence percentage of 82.7%. This shows that this financing has contributed greatly to the economic growth of the Padang Garugur Jae village community, especially small and medium businesses.